Extended Warranties, Maintenance Service and Lease Contracts Modeling and Analysis for Decision-Making - Murthy, D.N.Prabhakar.; Jack, Nat.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Serving to unify the existing literature on extended warranties, maintenance service contracts and lease contracts, this book also presents a unique perspective on the topic focussed on cost analysis and decision-making from the perspectives of the parties involved. Using a game theoretic approach together with mathematical modelling, results are presented in an integrated manner with key topics that require further research highlighted in order to serve as a starting point for researchers (engineers and statisticians) who are interested in doing further work in these areas. Designed to assist practitioners (managers, engineers, applied statisticians) who are involved with extended warranties, maintenance service contracts and lease contracts, the book provides them with the models and techniques needed for proper cost analysis and effective decision-making. The book is also suitable for use as a reference text in industrial engineering, applied statistics, operations research and management.
1.Introduction -- 2.Product Reliability and Maintenance -- 3.Introduction to Game and Agency Theories -- 4.EW/MSC An Overview -- 5.EW/MSC Process -- 6.Cost Analysis of EW/MSC -- 7.Models for EW/MSC Decision-making -- 8.Lease Contracts -- 9.Models for Lease Decision-making -- 10.Management of EW/MSC and Lease Processes -- 11.Risk Management.
Keywords: Engineering; Engineering economics; Engineering economy; Quality control; Reliability; Industrial safety; Industrial organization; Engineering; Engineering Economics, Organization, Logistics, Marketing; Quality Control, Reliability, Safety and Risk; Industrial Organization; Electronic books